Mexico's Seguro Popular: Achievements and Challenges - Antonio Chemor Ruiz; Anette Elena Ochmann Ratsch; Gloria Araceli Alamilla Martínez (Taylor & Francis Group, 2018)
In Mexico, Seguro Popular is a landmark government program aimed to guarantee universal access to health services, especially for the most vulnerable populations. Since its adoption in 2004, important changes have been made to improve the performance of Seguro Popular. In this article, we present the main changes that have been implemented in Seguro Popular during the current administration (2012-2018) and propose a series of considerations to improve its performance in the immediate future and thus contribute to achieving the goal of universal health coverage in Mexico.